Radiative recombination in initial and electron-irradiated GaP crystals - Hontaruk, O.; Konoreva, O.; Litovchenko, P.; Manzhara, V.; Opilat, V.; Pinkovska, M.; Tartachnyk, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Photoluminescence of GaP crystals irradiated by 1 MeV electrons was studied at 4.2 K. Samples were prepared using various technologies and doped by Te, Zn, Mg and N. Emission spectra were analyzed as dependent on the impurity content. Found was the electron irradiation influence on the luminescence intensity and its mechanism. Radiative recombination intensity was shown to recover efficiently within the temperature range 200-600 ºC, and the main annealing stage being at 200-400 ºC.